Європейські мережі обміну Інтернет-трафіком та їхній вплив на зв'язність між автономними системами - Зубок, В.Ю. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
The article dedicated to research of Europe’s largest network of Internet exchange DE-CIX using the routing tables of its participants. Also proposed a calculation methods for whole network and single node parameters such as degree distribution, clustering coefficient, average geodesic path, the global effectiveness and vulnerability.